Frei Damião de Bozzano: interpretação de uma devoção a partir do catolicismo popular. - Silva, Jociel João Gomes da (2021)
The object of our study is to make an interpretation of the devotion to Friar Damião de Bozzano, based on popular catholicism. The faithful's belief in the sanctity of this friar led to the establishment of a process in the Vatican for him to be officially declared a saint. But, even before that happens, the people already venerate him as such. We seek to understand this devotion based on historical elements, observing the facts that involved his missionary action in the Northeast of Brazil. For that, we analyzed the practices of this religious, since his arrival in Brazil in 1931 until his death in 1997. And throughout this period, we have seen the rise and consolidation of devotion around his figure. However, since his death, this devotion has been growing and is expressed, visibly, in the memorials dedicated to him. So, with this study, we tried to reflect on the contributions that can come from this devotion to evangelization today. For this purpose, we have several bibliographic and documentary sources and, even though we are aware of the possible gaps, they assure us in our objective of contributing so that this topic continues to be the object of research and discoveries and, with that, we perceive and value the rich diversity of expressions of popular religiosity. Regarding to the Brazilian Religious Basis, we start from the contributions of Bittencourt Filho, seeking to understand the formation of religiosity in the country. And to better understand the various forms of devotion to Friar Damião, at this time of deregulation of the faith, we have the contributions of Danièle Hervieu-Léger work. All this research and interpretation is intended to make the rich diversity of expressions of popular Catholicism noticeable and valued.